2021
DOI: 10.3390/jcm10214977
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ultrasonic Agitation on the Porosity Distribution in Apically Perforated Root Canals Filled with Different Bioceramic Materials and Techniques: A Micro-CT Assessment

Abstract: The present study evaluated the effect of ultrasonic agitation on the porosity distribution of BioRoot RCS/single gutta-percha cone (BR/SC) and MTA Flow (MF) root canals fillings used as apical plugs in moderately curved and apically perforated roots. Eighty mesial root canals of mandibular first molars were enlarged up to ProTaper NEXT X5 rotary instrument 2 mm beyond the apical foramen, simulating apical perforations. Specimens were randomly divided into four experimental groups (20 canals per group) accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
1
0
0
Order By: Relevance
“…The authors attributed this discrepancy in the studies to variations in MTA thickness. Consistent with the present study, Druktenis et al [64] reported an increase in porosity percentages when direct ultrasonic activation was applied for 10 s on various bioceramic materials. In this study, the manual technique allows for more controlled condensation, regardless of cavity size.…”
Section: Discussionsupporting
confidence: 92%
“…The authors attributed this discrepancy in the studies to variations in MTA thickness. Consistent with the present study, Druktenis et al [64] reported an increase in porosity percentages when direct ultrasonic activation was applied for 10 s on various bioceramic materials. In this study, the manual technique allows for more controlled condensation, regardless of cavity size.…”
Section: Discussionsupporting
confidence: 92%